A Case Report of Recurrent Hypokalemia During Pregnancies Associated With Nonaldosterone-Mediated Renal Potassium Loss. (May 2021) - Pintavorn, Pairach; Munie, Stephanie
Rationale: Geller et al reported a rare mutation in the mineralocorticoid receptor (MR) resulting in constitutive MR activity. Progesterone, normally an MR antagonist, acts as a potent agonist with this mutation. Progesterone levels can increase 100-fold during pregnancy and thus lead to increased MR activity in this setting, resulting in hypertension (HTN) and hypokalemia during pregnancy and resolution of hypokalemia after delivery. Presenting concerns: Our patient was a 33-year-old African American female with a history of pregnancy-induced HTN associated with hypokalemia during her last pregnancy. She presented with muscle weakness from profound hypokalemia complicated by nephrogenic diabetes insipidus (DI) and rhabdomyolysis. Diagnosis: Her admission potassium was 1.9 mmol/L (3.5-5.1 mmol/L) with a 24-hour urine potassium of 35 mmol per day and an unmeasurable serum aldosterone level. Her potassium normalized 1 day after delivery off potassium supplementation and amiloride, which were last given 1 day prior to her delivery. Recurrent hypokalemia from nonaldosterone-mediated renal potassium wasting during pregnancy (with normal potassium in a nongestational state) is consistent with the cases of gain-of-function mutation in MR that Geller et al report. A definite diagnosis requires genetic analysis. Interventions: Her hypokalemia was refractory to potassium replacement but quickly responded to an inhibitor of the epithelial sodium channel (ENaC), amiloride. Outcomes: Her potassium normalized on amiloride 10 mg per day and KCL 40 mEq daily during the remainder of her pregnancy, and her nephrogenic DI resolved after this correction of hypokalemia. After her delivery, her potassium remained normal off the potassium supplements and amiloride. Novel findings: Pregnancy-induced hypokalemia from an activating MR mutation has rarely been reported. Pregnancy-induced HTN is often the first differential diagnosis in a patient who develops worsening in her HTN during pregnancy. We should also consider the possibility of a gain-of-function mutation in MR in these patients who also have associated hypokalemia.